Educating nurses to care for military veterans in civilian hospitals: An integrated literature review. (December 2016) - Cooper, Linda; Andrew, Sharon; Fossey, Matt
Abstract: Background: In the UK, military veterans will receive care by civilian nurses in civilian hospitals. We propose that the nurses providing this care require an understanding of the unique experiences and specific health needs of veterans to deliver evidence-based care. Aim: To conduct an integrative review of published literature to explore how nursing programmes prepare nurses to care for the military veteran population in civilian hospitals. Review methods: A systematic search was undertaken of a range of electronic databases, Google Scholar and hand searching of Military and Veteran health journals. Papers that focused on education of civilian nurses about veteran health and included primary research or description of practice-based innovations were included in the review. Results: The search generated sixteen papers that were focused on nurse education in higher education institutions. Several papers focused on simulation as a teaching method for veteran-specific health issues or curriculum developments with educational innovations such as online courses. Six papers focusing in continuing professional education of nurses in the clinical setting were included as supplementary information. All papers reviewed were US focused and dated between January 2011 and September 2015. Our search concluded that there is a gap in knowledge in this subject area within a UK context, therefore our review includes UK background information to support the US findings. Conclusion: Civilian nurses need educational preparation to understand the specific needs of veterans. Educational institutions in the US have responded to nationwide initiatives to undertake that preparation. More empirical studies need to be undertaken to develop, test and evaluate educational innovations for preparing students and nurses delivering care to military veteran in civilian healthcare settings. Highlights: Military veterans may receive health care in civilian hospitals. Nurses working in civilian settings need an understanding of veteran-specific health issues. Few empirical studies are available about teaching nursing students veteran-specific needs.